Health management in frontier: integrative review on its impact for hospital care. - Formoso de Moraes, Gabriela; Silveira Cardoso, Leticia; Silveira da Rosa, Liane; Zavarese da Costa, Valdecir; Pinto dos Santos, Cristiano; Cezar-Vaz, Marta Regina (Revista de Pesquisa: Cuidado é Fundamental)
Objective: To identify the subsidies provided by scientific production to hospital health management in frontier areas. Methods: This is an integrative review that explored the universe of 24 articles indexed in the Virtual Health Library, the database of Latin American and Caribbean Health Sciences (LILACS). Results: Socioeconomic health management aspects at the border that showed the mobility of people and the management of health services and; clinical aspects of health management at the border which highlighted aspects of service and customer characteristics. Conclusion: Health in the frontier area explored in scientific production subsidizes the hospital management to indicate the socioeconomic factors as determinants of the health-disease. Determination which results in increased demand and the need for health diagnostic technology.